(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with vaginitis during the third trimester of pregnancy. Subjects and Methods: This study involved pregnant women in their third trimester who presented for examination and treatment at Ca Mau Obstetrics and Pediatrics Hospital from June 2024 to July 2025. Results: Statistically significant factors associated with vaginitis in the third trimester (p<0.05) included educational level, history of vaginitis, history of abortion, routine gynecological examination habits, and post-coital hygiene habits. Conclusion: Regarding socio-demographic characteristics, a high level of education (university level or above) was identified as a protective factor, significantly reducing the risk of infection compared to the lower-education group. In terms of obstetric history, a history of vaginitis and prior abortion were risk factors that increased the likelihood of infection in the current pregnancy. Regarding lifestyle habits, the study observed a statistically significant association among pregnant women practicing post-coital hygiene and undergoing routine gynecological examinations, with a higher prevalence of infection recorded in these groups.